(3JMQjQ cJGH eCNhPGJ CQTejOSs - (3GQTejOSs
(3ChdgG (B:s
(3bO eQ ai bhdfG ai GdCTcGd PhGJ GdCVdGY GdCQHYI HYO Pdc Yed GdhMjO GdbhHi ebGdg SeGgG QSe cJGH CQTejOS ai GdeCNhPGJ s
(3BNQgG (B:s
(3dCf RGhjI g` eKd RGhjI QW M ajchf NW Q W eSGhjkG dNW Qg` hPdc eG CQOfGg Je GdeCNhPGJ dCQTejOS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1455s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs